Light conversion adhesive film based on quinoxaline system light conversion material
By using a light-transforming material based on a quinoxaline system in a solar cell device, the problem of low UV light utilization efficiency in the prior art is solved, and higher photoelectric conversion efficiency and battery life are achieved.
Patent Information
- Application Number
- CN202411969157.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing solar cell devices have low efficiency in utilization of ultraviolet light, resulting in a decrease in battery efficiency and life, especially for HJT batteries, which is more prominent.
Using a light-transforming material based on the quinoxaline system, a quinoxaline with a structure similar to that of the triazole is used as the nucleus, the conjugated monomer is linked to form a fully conjugated skeleton, and the side chain is used to adjust the absorption and emission spectrum to improve the light-transforming efficiency.
Effectively absorb ultraviolet and blue-violet light in sunlight, converting it into blue fluorescence, improving the photoelectric conversion efficiency and life of solar cells, while reducing sensitivity to ultraviolet light.
Smart Images

Figure CN119752353A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar cell materials, and in particular relates to a light-converting adhesive film based on a quinoxaline system light-converting material. Background Art
[0002] As a clean energy with abundant resources and no need for transportation, solar energy is expected to become an alternative energy source to replace traditional fossil fuels. Therefore, the development of solar energy collection and conversion technology has gradually become the focus of national and social attention. Photovoltaic devices can directly convert solar energy into electrical energy, which is one of the most effective ways to utilize solar energy. So far, the demand for photovoltaic installed capacity around the world is still increasing. Since most photovoltaic devices can only effectively utilize visible light and near-infrared light in sunlight, the utilization efficiency of ultraviolet light (wavelength less than 400nm) in sunlight is low. Not only that, the presence of ultraviolet light in sunlight will also reduce the service life of photovoltaic devices, especially for heterojunction (HJT) cells that are expected to replace PERC and TOPCon as the third generation of solar cells. Therefore, converting ultraviolet and blue-violet light into visible light that can be used by silicon cells can simultaneously improve the efficiency and life of the cells. This conversion can be achieved by introducing fluorescent or phosphorescent light conversion materials into the adhesive film. At present, such light conversion adhesive films have been increasingly widely used in the encapsulation of solar cells.
[0003] The use of wavelength conversion film can not only effectively absorb the ultraviolet light in sunlight to avoid damage to the service life of photovoltaic devices; it can also convert ultraviolet light into usable visible light, thereby improving the photoelectric conversion efficiency of photovoltaic devices. The technical core of wavelength conversion film lies in the selection of suitable light converters. The current light converters are mainly divided into inorganic light converters and organic light converters. Compared with inorganic light converters, organic light converters have the advantages of low price, wide variety, and easy performance control. In addition, since the substrate of the wavelength conversion film belongs to organic polymer materials, the organic light converter and the substrate often show better dispersibility and compatibility, and have less effect on the light transmittance of the wavelength conversion film. Conventional organic light converters are some down-converting organic luminescent small molecules, which can well realize the absorption of ultraviolet light and convert it into visible light (generally blue light or sky blue light), and organic light converters are often natural light converter materials, but most organic light converters have poor stability, and the corresponding adhesive films usually have high water vapor permeability, which greatly reduces the service life of photovoltaic modules.
[0004] At present, there is still a lot of room for improvement in light-reflecting films. First of all, the wavelength of light converted by mass-produced light-reflecting films is distributed around 420nm, which is not the wavelength with the highest EQE response of HJT cells. Further increasing the wavelength of the converted light to above 500nm can increase the power of the component. Secondly, since the maximum absorption wavelength is around 345nm, a large part of the ultraviolet light will still pass through the film to the battery cell, causing damage to the battery cell.
[0005] Therefore, there is a need in the art for a light conversion adhesive film for sunlight wavelength conversion that can more effectively improve the efficiency and life of solar cells. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention proposes a light-converting adhesive film based on a quinoxaline system light-converting material. In the present invention, quinoxaline is used as the core, which is similar to the structure of triazole and has good weather resistance. At the same time, conjugated monomers are linked to form a main structure with a fully conjugated skeleton, and side chains that help dissolution are used to form a light-converting material based on the quinoxaline system. The material synthesis in the present invention is simple, and the raw material cost is low. It can adjust the range of the absorption spectrum and selectively absorb the wavelength band of ultraviolet light, and can also adjust the range of the emission spectrum, adjusting the emission spectrum to the range of the relatively high EQE of HJT, thereby improving the power of the component.
[0007] Specifically, one aspect of the present invention provides an organic compound:
[0008]
[0009] In formula I, Ar is selected from a substituted or unsubstituted C6-C14 arylene group, a substituted or unsubstituted 5-14 membered heteroarylene group having one or more heteroatoms selected from N, O, Se and S;
[0010] The term "substituted" means that one or more hydrogen atoms on the group are replaced by one or more substituents selected from halogen atoms, carboxyl groups, amine groups, ester groups, amide groups, C1-C10 alkoxy groups, cyano groups, nitro groups and azido groups;
[0011] R1, R2, R5 and R6 are each independently selected from C1-C20 alkyl, C1-C20 alkoxy, C1-C20 alkyl substituted by C1-C20 alkoxy and the functional group shown in formula II In Formula II, n ≥ 2, * represents the linking site to the other parts of the organic compound;
[0012] R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C10 alkoxy group, a C1-10 alkylthio group, a carboxyl group, an amine group, an ester group, an amide group, a cyano group, a nitro group and an azido group.
[0013] In one or more embodiments, the organic compound has one or more of the following characteristics:
[0014] Ar is selected from the following functional groups: wherein R is a hydrogen atom, a halogen atom, a carboxyl group, an amine group, an ester group, an amide group, a C1-C10 alkoxy group, a cyano group, a nitro group or an azido group, X is O, S or Se, and the aromatic ring of the functional group has two connection sites for connecting to other parts of the organic compound;
[0015] R1 and R2 are each independently selected from C1-C10 alkyl and C1-C10 alkoxy;
[0016] R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C10 alkoxy group, a C1-10 alkylthio group, an ester group and a cyano group;
[0017] R5 and R6 are each independently selected from C1-C20 alkyl groups.
[0018] In one or more embodiments, the organic compound has one or more of the following characteristics:
[0019] Ar Wherein, * indicates the connection site where Ar is connected to other parts of the organic compound;
[0020] R1 and R2 are each independently selected from C1-C4 alkyl and C1-C4 alkoxy;
[0021] R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C4 alkoxy group, a C1-C4 alkylthio group, an ester group and a cyano group; R5 and R6 are each independently selected from a C1-C10 alkyl group.
[0022] In one or more embodiments, the I compound is selected from one or more of compounds 1-9:
[0023]
[0024] Another aspect of the present invention provides a light conversion adhesive film for sunlight wavelength conversion, the light conversion adhesive film comprising the organic compound in any one of the embodiments described herein and a matrix.
[0025] In one or more embodiments, the mass fraction of the organic compound in the light conversion adhesive film is 0.01% to 5%.
[0026] In one or more embodiments, the mass fraction of the organic compound in the light conversion adhesive film is 0.2% to 0.5%.
[0027] In one or more embodiments, the organic compound has an absorption range of 280 to 400 nm, and a maximum absorption peak of 320 to 380 nm.
[0028] In one or more embodiments, the photoluminescence range of the organic compound is 400 to 600 nm, and the maximum emission peak is 450 to 550 nm.
[0029] In one or more embodiments, the thickness of the light conversion adhesive film is 0.1 to 1.0 mm.
[0030] In one or more embodiments, the light conversion adhesive film further comprises one or more auxiliary agents selected from the group consisting of a cross-linking agent, a co-cross-linking agent, a silane coupling agent, a plasticizer, an antioxidant, and a water absorbent.
[0031] In one or more embodiments, the light conversion adhesive film further includes a matrix.
[0032] In one or more embodiments, the matrix is one or more selected from polyethylene oxide, ethylene-vinyl acetate copolymer, polyvinyl butyral, ethylene-octene copolymer, and silicone resin.
[0033] In one or more embodiments, the refractive index of the matrix is 1.4 to 1.7;
[0034] Another aspect of the present invention provides a method for preparing the light-converting adhesive film described in any embodiment of the present invention, the method comprising: uniformly mixing the components of the light-converting adhesive film, melt-extruding into a film, and cooling and shaping to obtain the light-converting adhesive film.
[0035] Another aspect of the present invention provides a solar cell assembly, which includes a solar cell and a light conversion adhesive film according to any embodiment of the present invention disposed on at least one surface of the solar cell.
[0036] In one or more embodiments, the solar cell assembly includes one or more of the following cells: PN cells containing III-V or II-IV group elements, Cu-In-Ga-Se thin film cells, organic sensitizer cells, organic thin film cells, quantum dot thin film cells, perovskite cells, perovskite / crystalline silicon stacked cells, amorphous silicon solar cells, microcrystalline silicon solar cells and crystalline silicon solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the structural position of the light transfer adhesive film in the battery assembly according to the embodiment of the present invention. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.
[0039] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0040] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0041] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0042] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0043] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined by the present invention.
[0044] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0045] The quinoxaline used in the present invention is a fluorescent group with strong absorption in the ultraviolet region. It has quinoxaline as the core, is similar to the triazole structure, has good weather resistance, and simultaneously links conjugated monomers to form a main structure with a fully conjugated structure, and is matched with a side chain that helps dissolve to form a light-converting material based on the quinoxaline system. The material synthesis in the present invention is simple, the raw material cost is low, and the HOMO energy level of the material can be effectively improved by introducing an electron-donating functional group to narrow the band gap. This strategy can not only adjust the range of the absorption spectrum, selectively absorb the wavelength band of ultraviolet light, and red-shift the absorption spectrum; it can also adjust the range of the emission spectrum, adjust the emission spectrum to the interval range of the relatively high EQE of HJT, and red-shift the fluorescence emission spectrum to increase the power of the component. The present invention adds a light-converting material based on quinoxaline to the adhesive film. This material can effectively absorb ultraviolet light and blue-violet light in sunlight and convert it into blue fluorescence for use in batteries. The material itself is stable to ultraviolet light and is not easy to decompose, so it can effectively prevent the battery components from being damaged by ultraviolet light, and improve the efficiency and life of the battery.
[0046] The main body of the light-converting material in the light-converting adhesive film of the present invention is constructed of quinoxaline. The mass fraction of the light-converting material in the light-converting adhesive film can be 0.01% to 5%. Controlling the amount of the light-converting material selected in the light-converting adhesive film of the present invention within the aforementioned preferred range is conducive to improving the effect of the light-converting adhesive film in enhancing the efficiency and stability of the battery.
[0047] In some embodiments, the schematic diagram of the structure position of the light-converting adhesive film in the battery assembly of the present invention is as follows Figure 1 As shown, the light-converting adhesive film is wrapped around the outer surface of the cell, and is covered with glass panels on the upper and lower layers.
[0048] Furthermore, the light conversion adhesive film of the present invention may optionally or preferably include auxiliary agents. Available auxiliary agents include but are not limited to cross-linking agents, auxiliary cross-linking agents, plasticizers, antioxidants, water absorbents, and the like.
[0049] In some embodiments, the light conversion adhesive film of the present invention is composed of a light conversion material, a matrix and an optional auxiliary agent.
[0050] Organic compounds
[0051] In the present invention, the structure of the organic compound used as the light conversion material is as follows:
[0052]
[0053] In Formula I,
[0054] Ar is selected from substituted or unsubstituted C6-C14 arylene, substituted or unsubstituted 5-14 membered heteroarylene having one or more heteroatoms selected from N, O, Se and S;
[0055] The term "substituted" means that one or more hydrogen atoms on the group are replaced by one or more substituents selected from halogen atoms, carboxyl groups, amine groups, ester groups, amide groups, C1-C10 alkoxy groups, cyano groups, nitro groups and azido groups;
[0056] R1, R2, R5 and R6 are each independently selected from C1-C20 alkyl, C1-C20 alkoxy, C1-C20 alkyl substituted by C1-C20 alkoxy and the functional group shown in formula II In Formula II, n ≥ 2, * represents the linking site to the other parts of the organic compound;
[0057] R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C10 alkoxy group, a C1-10 alkylthio group, a carboxyl group, an amine group, an ester group, an amide group, a cyano group, a nitro group and an azido group.
[0058] In the present invention, an alkyl group refers to a monovalent saturated group having a straight or branched structure composed of carbon atoms and hydrogen atoms. In the present invention, the number of C before the group represents the number of carbon elements contained in the group, for example, a C1 alkyl group represents an alkyl group containing 1 carbon atom, i.e., a methyl group. The alkyl group applicable to the present invention can be a C1 to C20 alkyl group, for example, a C1 alkyl group, a C2 alkyl group, a C3 alkyl group, a C4 alkyl group, a C5 alkyl group, a C6 alkyl group, a C7 alkyl group, a C8 alkyl group, a C9 alkyl group, a C10 alkyl group, a C11 alkyl group, a C12 alkyl group, a C13 alkyl group, a C14 alkyl group, a C15 alkyl group, a C16 alkyl group, a C17 alkyl group, a C18 alkyl group, a C19 alkyl group, and a C20 alkyl group.
[0059] In the present invention, an alkoxy group refers to an -O-alkyl group.
[0060] In the present invention, an alkylthio group refers to an -S-alkyl group.
[0061] In the present invention, an ester group refers to a functional group containing a -(C=O)-O- group. The number of carbon atoms contained in the ester group may be 1 to 20, such as 1 to 10, 1 to 4. In some embodiments, the ester group is -(C=O)-O-CH3.
[0062] In the present invention, aryl refers to a monovalent group having an aromatic ring structure composed of carbon atoms and hydrogen atoms, and the aryl is connected to other parts of the molecule through the carbon atoms on the aromatic ring. The aryl suitable for the present invention is a C6 aryl, such as phenyl.
[0063] In the present invention, heteroaryl refers to a monovalent group having an aromatic ring structure composed of carbon atoms, hydrogen atoms and heteroatoms (such as sulfur atoms, nitrogen atoms, oxygen atoms), and the heteroaryl is connected to other parts of the molecule through carbon atoms or heteroatoms on the aromatic ring. The heteroaryl suitable for the present invention can be a C5-C6 aryl, such as pyridyl, furyl, thienyl, selenophene or pyrrolyl.
[0064] In the present invention, alkyl, alkoxy, aryl and heteroaryl groups may be substituted by other substituents, including but not limited to halogen atoms, carboxyl groups, amine groups, ester groups, amide groups, alkoxy groups, nitro groups and azido groups.
[0065] In the present invention, the halogen atom includes fluorine, chlorine, bromine and iodine.
[0066] In the present invention, an amine group refers to -NR a R b , R a and R b Each is independently selected from H, C1-C10 alkyl, C2-C10 alkenyl and C2-C10 alkynyl.
[0067] In some preferred embodiments, Ar is selected from phenyl, pyridyl, furyl, thienyl, selenophenyl or pyrrolyl; R1 and R2 are each independently selected from C1-C4 alkyl and structure II: In formula II, n≥2, for example, methyl, ethyl, n-propyl, isopropyl, tert-butyl, isobutyl; R3 and R4 are each independently selected from C1-C4 alkoxy, C1-C4 alkylthio, ester, cyano and the structure of formula II in which the "*" position is substituted by an oxygen atom or a sulfur atom, such as methaneoxy, ethaneoxy, n-propaneoxy, isopropaneoxy, n-butaneoxy, isobutaneoxy, tert-butaneoxy, methanethio, ethanethio, n-propanethio, isopropanethio, n-butanethio, isobutanethio, tert-butanethio; R5 and R6 are each independently selected from C1-C13 alkyl and the structure of formula II: In formula II, n≥2, for example, methyl, ethyl, n-propyl, isopropyl, tert-butyl, isopentyl, 3-ethyl-heptyl, 3-butyl-nonyl.
[0068] In some preferred embodiments, Ar is selected from phenyl, R1 and R2 are each independently selected from tert-butyl and isobutoxy, R3 and R4 are each independently selected from fluorine atoms, hydrogen atoms, methanethio, methanesulfonyl, and cyano, R5 and R6 are both selected from isobutyl.
[0069] In some preferred embodiments, Ar is selected from furanyl, R1 and R2 are each independently selected from tert-butyl and isobutanyloxy, R3 and R4 are each independently selected from fluorine atoms, hydrogen atoms, methoxy, methylthio, and cyano, R5 and R6 are both selected from isobutyl.
[0070] In some preferred embodiments, Ar is selected from thienyl, R1 and R2 are each independently selected from tert-butyl and isobutoxy, R3 and R4 are each independently selected from fluorine atoms, hydrogen atoms, methoxy, methoxy, and cyano, R5 and R6 are both selected from isobutyl.
[0071] Compound 1, Compound 2, Compound 3, Compound 4, Compound 5, Compound 6, Compound 7, Compound 8 and Compound 9
[0072]
[0073] In some preferred embodiments, the light-converting adhesive film of the present invention comprises one or more compounds selected from Compound 1, Compound 2, Compound 3, Compound 4, Compound 5, Compound 6, Compound 7, Compound 8 and Compound 9 as light-converting materials and a matrix.
[0074] In some preferred embodiments, the light conversion material is selected from compound 4. This is beneficial to improving the light conversion efficiency of the light conversion adhesive film.
[0075] In the present invention, the hydrogen atoms in Compound 1, Compound 2, Compound 3, Compound 4, Compound 5, Compound 6, Compound 7, Compound 8 and Compound 9, which are light conversion materials, may be protium or deuterium.
[0076] Source of compound
[0077] The organic compounds, Compound 1 to Compound 9, can be purchased from commercial sources.
[0078] Matrix
[0079] In the present invention, the matrix is preferably transparent to visible light. When the transmittance of the matrix to visible light is ≥ 0.85, the matrix can be considered to be transparent to visible light.
[0080] The material of the matrix is a polymer material, including but not limited to: polyethylene oxide, polyvinyl butyral, ethylene-vinyl acetate copolymer, silicone resin, polyethylene terephthalate, polyethylene, ethylene polytetrafluoroethylene, polyimide, polycarbonate, polystyrene, polyurethane, polyacrylate, silicone sol-gel, polyolefin elastomer, and combinations thereof.
[0081] The refractive index of the matrix is preferably 1.4 to 1.7, such as 1.4, 1.5, 1.6, or 1.7, which is beneficial to improving the effect of the light conversion film on enhancing the efficiency and stability of the battery.
[0082] The mass fraction of the matrix in the light-converting adhesive film can be 80% to 99.8%, for example, 90%, 95%, 96%, 97%, 98%, 98.5%, 98.9%, 99%, 99.5%.
[0083] Additives
[0084] The auxiliary agents suitable for use in the present invention include, but are not limited to, crosslinking agents, auxiliary crosslinking agents, plasticizers, antioxidants, water absorbents, and the like.
[0085] In some preferred embodiments, the auxiliary agent includes a crosslinking agent, such as tert-butyl peroxycarbonate-2-ethylhexyl ester. The mass fraction of the crosslinking agent in the light conversion film is preferably 0.1% to 1%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%.
[0086] In some preferred embodiments, the auxiliary agent includes a silane coupling agent, such as γ-methacryloxypropyltrimethoxysilane. The mass fraction of the silane coupling agent in the light-converting adhesive film is preferably 0.1% to 1%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%.
[0087] In some preferred embodiments, the auxiliary agent includes an antioxidant, such as antioxidant 1076. The mass fraction of the antioxidant in the light conversion film is preferably 0.1% to 1%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%.
[0088] In the present invention, plasticizers, antioxidants and water absorbents are optionally or preferably added to the light conversion adhesive film, and the amounts used can be conventional.
[0089] In some embodiments, the thickness of the light conversion adhesive film of the present invention is 0.1-1.0 mm, for example, 0.1 mm, 0.3 mm, 0.5 mm, 0.7 mm, 1.0 mm.
[0090] In some embodiments, the absorption range of the light conversion material is 280 nm to 400 nm, and the maximum absorption peak is 320 to 380 nm.
[0091] In some embodiments, the photoluminescence of the light conversion material is 400-600 nm, and the maximum emission peak is 450-550 nm.
[0092] Preparation method of light-converting adhesive film
[0093] The light-converting adhesive film of the present invention can be prepared by uniformly mixing the components of the light-converting adhesive film, melting and extruding the mixture into a film, and cooling and shaping the film.
[0094] The temperature of melt extrusion may be 80 to 120° C., for example, 90° C., 100° C., or 110° C. Cooling and shaping may be performed at room temperature (for example, 25° C.).
[0095] Solar cell modules
[0096] In a high temperature and negative pressure environment, the light-converting adhesive film of the present invention is used as a front adhesive film and is laminated and packaged with a solar cell (such as a monocrystalline silicon solar cell) and a back adhesive film (the material can be pure EVA) on a back plate (such as a glass plate). After the component is cooled, the light-converting adhesive film becomes the front surface of the component, and the back adhesive film becomes the back surface of the component, thereby obtaining a solar cell component.
[0097] In some preferred embodiments, the solar cell module includes at least one of the following cells: a PN cell containing III-V or II-IV group elements, a Cu-In-Ga-Se (CIGS) thin film cell, an organic sensitizer cell, an organic thin film cell, a quantum dot thin film cell, an amorphous silicon solar cell, a microcrystalline silicon solar cell, and a crystalline silicon solar cell.
[0098] The present invention uses a quinoxaline-based light-conversion material to make the material and the film both efficient and stable. The present invention has the following beneficial technical effects:
[0099] The quinoxaline used in the present invention is a fluorescent group with strong absorption in the ultraviolet region. It uses quinoxaline as the core, is similar to the triazole structure, has good weather resistance, and simultaneously links conjugated monomers to form a main structure with a fully conjugated structure, and is matched with a side chain that helps dissolve to form a light-converting material based on the quinoxaline system. The material synthesis in the present invention is simple, the raw material cost is low, and it can not only adjust the range of the absorption spectrum, selectively absorb the wavelength band of ultraviolet light, but also adjust the range of the emission spectrum, and adjust the emission spectrum to the interval range of the relatively high EQE of HJT, thereby improving the component power. The present invention adds a light-converting material based on quinoxaline to the adhesive film. Such a material can effectively absorb ultraviolet light and blue-violet light in sunlight and convert it into blue fluorescence for use in batteries. The material itself is stable to ultraviolet rays and is not easy to decompose, so it can effectively prevent the battery components from being damaged by ultraviolet rays, thereby improving the efficiency and life of the battery.
[0100] The present invention will be described below in the form of specific examples. It should be understood that these examples are illustrative only and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The compounds in the examples can all be purchased through commercial routes.
[0101] Compound 1-9 was prepared by the following method:
[0102] 1mmol of 4,7-dibromobenzoquinoxaline derivative and 3mmol of 4-alkylphenylboronic acid were dissolved in 10mL of 1,4-dioxane, and 2mmol of potassium carbonate and 1mL of deionized water were added thereto. Then, the reaction system was placed in an environment filled with nitrogen or argon, and the reaction system was heated to 95°C. After reacting for 24 hours, the reaction system was cooled to room temperature, quenched with water, extracted with dichloromethane, dried by rotation, and purified by column chromatography to obtain the target product in the form of white powder. The results of its hydrogen nuclear magnetic resonance spectrum are as follows.
[0103] Compound 1: 1 H NMR (500MHz, Chloroform-d) δ = 7.46–7.40 (m, 2H), 7.37–7.32 (m, 2H), 2.71 (d, J = 7.0, 2H), 2.14 (dh, J = 13.7, 6.9, 1H), 1.35 (s, 9H), 0.96 (d, J = 6.8, 6H).
[0104] Compound 2: 1 H NMR(500MHz,Chloroform-d)δ=8.01(s,1H),7.92–7.86(m,2H),7.59–7.53(m,2H) ,2.70(d,J=7.1,2H),2.14(dh,J=13.5,6.8,1H),1.34(s,9H),0.96(d,J=6.8,6H).
[0105] Compound 3: 1 H NMR(500MHz,Chloroform-d)δ=7.84(s,1H),7.51–7.45(m,1H),7.04–6.98(m,1H),3.80(d,J=7.1,1 H), 2.70 (d, J = 7.0, 1H), 2.11 (ddq, J = 40.7, 13.7, 6.8, 1H), 1.03 (d, J = 6.8, 3H), 0.96 (d, J = 6.8, 3H).
[0106] Compound 4: 1 H NMR(500MHz,Chloroform-d)δ=7.47–7.42(m,1H),7.04–6.99(m,1H),3.79(d,J=7.0,1H),3.73(s,2 H), 2.69 (d, J = 7.0, 1H), 2.10 (ddq, J = 43.7, 13.7, 6.8, 1H), 1.03 (d, J = 6.8, 3H), 0.96 (d, J = 6.8, 3H).
[0107] Compound 5: 1H NMR(500MHz,Chloroform-d)δ7.64–7.58(m,2H),7.39–7.33(m,2H),2.81(d,J =7.8Hz,2H),2.56(s,2H),2.13(dp,J=15.1,7.5Hz,1H),0.93(d,J=7.3Hz,6H).
[0108] Compound 6: 1 H NMR(500MHz,Chloroform-d)δ7.65–7.59(m,2H),7.41–7.35(m,2H),3.88(s,2 H), 2.81 (d, J = 7.8Hz, 2H), 2.13 (dp, J = 15.1, 7.5Hz, 1H), 0.93 (d, J = 7.3Hz, 6H).
[0109] Compound 7: 1 H NMR (500MHz, Chloroform-d) δ7.52–7.46(m,2H),7.30–7.24(m,2H),2.81(d,J=7.8Hz,2H),2.13(dp,J=15.1,7.5Hz,1H),0.93(d,J=7.3Hz,6H).
[0110] Compound 8: 1 H NMR(500MHz,Chloroform-d)δ7.97(s,1H),7.40(s,1H),6.91(dt,J=7.0,0.9Hz,1H),2.81(d,J=7.7Hz,2H), 2.67(dd,J=6.0,0.9Hz,2H),2.13(dp,J=15.1,7.5Hz,1H),1.93–1.82(m,1H),0.92(dd,J=11.8,6.9Hz,12H).
[0111] Compound 9: 1 H NMR(500MHz,Chloroform-d)δ7.97(s,1H),6.84(d,J=5.7Hz,1H),6.29(dt,J=5.7,0.9Hz,1H),2.81(d,J=7.8Hz, 2H), 2.68 (dd, J=6.3, 0.9Hz, 2H), 2.13 (dp, J=15.1, 7.5Hz, 1H), 2.06–1.94 (m, 1H), 0.93 (dd, J=7.0, 2.3Hz, 12H).
[0112] Example 1
[0113] This embodiment provides a method of using compound 1 The light-converting adhesive film and corresponding devices are made of light-converting materials. In this embodiment, the light-converting adhesive film is manufactured by the following method:
[0114] According to the total mass of the light-converting adhesive film, 98% wt of ethylene-vinyl acetate copolymer (EVA), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570), 0.2% wt of compound 1 and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100° C. to form a film, and the extruded film was cooled and shaped at 25° C. to obtain a light-converting adhesive film with a thickness of 0.3 mm.
[0115] This embodiment manufactures a solar cell module in the following manner:
[0116] Under a negative pressure environment of 130°C, the encapsulating glass, the above-mentioned light-converting adhesive film, a 182mm HJT solar cell (purchased from Huasheng New Energy Technology Co., Ltd.), pure EVA and a glass backplane were laminated and packaged, and the light-converting adhesive film was used as the front surface of the cell to obtain the solar cell module of Example 1.
[0117] Example 2
[0118] This embodiment provides a compound 2 The invention relates to adhesive films and corresponding devices of light conversion materials.
[0119] This embodiment manufactures the light-converting adhesive film in the following manner:
[0120] According to the total mass of the light-converting film, 99.5%wt of ethylene-octene copolymer and 0.5%wt of compound 2 were mixed evenly, and then melt-extruded at 100°C to form a film. The extruded film was cooled and shaped at 25°C to obtain a light-converting film with a thickness of 0.3 mm.
[0121] This embodiment adopts the same method as that of embodiment 1 to prepare the solar cell assembly of embodiment 2.
[0122] Example 3
[0123] This embodiment provides a method of using compound 3 The invention relates to adhesive films and corresponding devices of light conversion materials.
[0124] This embodiment manufactures the light-converting adhesive film in the following manner:
[0125] According to the total mass of the light-converting film, 99% wt of silicone resin, 0.5% wt of compound 3 and 0.5% wt of antioxidant 1076 were mixed evenly, melt-extruded at 100°C to form a film, and the extruded film was cooled and shaped at 25°C to obtain a light-converting film with a thickness of 0.3 mm.
[0126] This embodiment adopts the same method as that of embodiment 1 to prepare the solar cell assembly of embodiment 3.
[0127] Example 4
[0128] This embodiment provides a method of treating a The invention relates to adhesive films and corresponding devices of light conversion materials.
[0129] This embodiment manufactures the light-converting adhesive film in the following manner:
[0130] According to the total mass of the light-converting film, 99% wt of silicone resin, 0.5% wt of compound 4 and 0.5% wt of antioxidant 1076 were mixed evenly, melt-extruded at 100°C to form a film, and the extruded film was cooled and shaped at 25°C to obtain a light-converting film with a thickness of 0.3 mm.
[0131] This embodiment adopts the same method as that of embodiment 1 to prepare the solar cell assembly of embodiment 4.
[0132] Example 5
[0133] This embodiment provides a compound 5 The light-converting adhesive film and corresponding devices are made of light-converting materials. In this embodiment, the light-converting adhesive film is manufactured by the following method:
[0134] According to the total mass of the light-converting adhesive film, 98% wt of ethylene-vinyl acetate copolymer (EVA), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570), 0.2% wt of compound 5 and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100° C. to form a film, and the extruded film was cooled and shaped at 25° C. to obtain a light-converting adhesive film with a thickness of 0.3 mm.
[0135] This embodiment manufactures a solar cell module in the following manner:
[0136] Under a negative pressure environment of 130°C, the encapsulating glass, the above-mentioned light-converting adhesive film, a 182mm HJT solar cell (purchased from Huasheng New Energy Technology Co., Ltd.), pure EVA and a glass backplane were laminated and packaged, and the light-converting adhesive film was used as the front surface of the cell to obtain the solar cell module of Example 5.
[0137] Example 6
[0138] This embodiment provides a method of using compound 6 The light-converting adhesive film and corresponding devices are made of light-converting materials. In this embodiment, the light-converting adhesive film is manufactured by the following method:
[0139] According to the total mass of the light-converting adhesive film, 98% wt of ethylene-vinyl acetate copolymer (EVA), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570), 0.2% wt of compound 6 and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100°C to form a film, and the extruded film was cooled and shaped at 25°C to obtain a light-converting adhesive film with a thickness of 0.3 mm.
[0140] This embodiment manufactures a solar cell module in the following manner:
[0141] Under a negative pressure environment of 130°C, the encapsulating glass, the above-mentioned light-converting adhesive film, a 182mm HJT solar cell (purchased from Huasheng New Energy Technology Co., Ltd.), pure EVA and a glass backplane were laminated and packaged, and the light-converting adhesive film was used as the front surface of the cell to obtain the solar cell module of Example 6.
[0142] Example 7
[0143] This embodiment provides a method of treating a The light-converting adhesive film and corresponding devices are made of light-converting materials. In this embodiment, the light-converting adhesive film is manufactured by the following method:
[0144] According to the total mass of the light-converting adhesive film, 98% wt of ethylene-vinyl acetate copolymer (EVA), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570), 0.2% wt of compound 7 and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100°C to form a film, and the extruded film was cooled and shaped at 25°C to obtain a light-converting adhesive film with a thickness of 0.3 mm.
[0145] Example 8
[0146] This embodiment provides a method of treating a The light-converting adhesive film and corresponding devices are made of light-converting materials. In this embodiment, the light-converting adhesive film is manufactured by the following method:
[0147] According to the total mass of the light-converting adhesive film, 98% wt of ethylene-vinyl acetate copolymer (EVA), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyltrimethoxysilane (KH570), 0.2% wt of compound 8 and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100°C to form a film, and the extruded film was cooled and shaped at 25°C to obtain a light-converting adhesive film with a thickness of 0.3 mm.
[0148] Example 9
[0149] This embodiment provides a method of treating a The light-converting adhesive film and corresponding devices are made of light-converting materials. In this embodiment, the light-converting adhesive film is manufactured by the following method:
[0150] According to the total mass of the light-converting adhesive film, 98% wt of ethylene-octene copolymer (POE), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570), 0.2% wt of compound 9 and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100° C. to form a film, and the extruded film was cooled and shaped at 25° C. to obtain a light-converting adhesive film with a thickness of 0.3 mm.
[0151] This embodiment manufactures a solar cell module in the following manner:
[0152] Under a negative pressure environment of 130°C, the encapsulating glass, the above-mentioned light-converting adhesive film, a 182mm HJT solar cell (purchased from Huasheng New Energy Technology Co., Ltd.), pure EVA and a glass backplane were laminated and packaged, and the light-converting adhesive film was used as the front surface of the cell to obtain the solar cell module of Example 9.
[0153] Comparative Example 1
[0154] This embodiment provides a film and a corresponding device using 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole as a UV cutoff material. This embodiment manufactures the cutoff film by the following method:
[0155] According to the total mass of the cut-off film, 98% wt of ethylene-octene copolymer (POE), 0.3% wt of tert-butyl peroxycarbonate-2-ethylhexyl ester (TBEC) as a cross-linking agent, 0.3% wt of silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570), 0.2% wt of 2-(2'-hydroxy-5'-tert-octylphenyl) and 0.2% wt of antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed evenly, melt-extruded at 100° C. to form a film, and the extruded film was cooled and shaped at 25° C. to obtain a light-converting film with a thickness of 0.3 mm.
[0156] This embodiment manufactures a solar cell module in the following manner:
[0157] Under a negative pressure environment of 130°C, the encapsulating glass, the above-mentioned cutoff film, 182mm HJT solar cells (purchased from Huasheng New Energy Technology Co., Ltd.), pure EVA and a glass backplane were laminated and packaged, and the light-converting film was used as the front surface of the cell to obtain the solar cell module of Comparative Example 1.
[0158] Test Case
[0159] 1. Photophysical property test: The photophysical test of the light-converting adhesive film in each embodiment was carried out using a UV-visible spectrometer and a fluorescence photometer. The absorption spectrum of the light-converting adhesive film was measured by an Agilent Cary 3500 UV-visible spectrophotometer, and the emission spectrum of the light-converting adhesive film was measured by a Horiba spectrometer FL-3. The results are shown in Table 1.
[0160] 2. Device performance test: In order to evaluate the performance of the solar cell module and illustrate the effect of the present invention, the solar cell module packaging material in each embodiment is tested for light conversion efficiency. The light conversion efficiency can be obtained by calibrating the number of incident photons, using an integrating sphere to test the number of emitted photons, and finally performing ratio calculation. The specific test method is referred to the "General Detection Method for Absolute Measurement of Photoluminescence Quantum Efficiency of Fluorescent Materials". The test results are shown in Table 1.
[0161] As can be seen from Table 1, the solar cells assembled from compounds 1-9 in their examples all have high light conversion efficiency, and Example 4 has the best light conversion efficiency. However, in Comparative Example 1, because the materials included do not have the property of fluorescence, the components of Comparative Example 1 can only prevent ultraviolet rays from entering, and cannot convert ultraviolet rays into visible light that can be used by photovoltaic cells. Therefore, the components based on Comparative Example 1 will have a certain power loss.
[0162] Table 1 Spectrum and performance test results of the embodiment
[0163] Example Maximum absorption wavelength Maximum emission wavelength Light conversion efficiency Example 1 355 415 88% Example 2 360 420 95% Example 3 365 425 94% Example 4 370 430 96% Example 5 368 427 95% Example 6 335 365 80% Example 7 325 346 50% Example 8 368 428 80% Example 9 363 424 70% Comparative Example 1 370 none none
Claims
1. An organic compound, characterized in that The structure of the organic compound is shown in Formula I: In formula I, Ar is selected from a substituted or unsubstituted C6-C14 arylene group, a substituted or unsubstituted 5-14 membered heteroarylene group having one or more heteroatoms selected from N, O, Se and S; The term "substituted" means that one or more hydrogen atoms on the group are replaced by one or more substituents selected from halogen atoms, carboxyl groups, amine groups, ester groups, amide groups, C1-C10 alkoxy groups, cyano groups, nitro groups and azido groups; R1, R2, R5 and R6 are each independently selected from C1-C20 alkyl, C1-C20 alkoxy, C1-C20 alkyl substituted by C1-C20 alkoxy and the functional group shown in formula II In Formula II, n ≥ 2, * represents the linking site to the other parts of the organic compound; R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C10 alkoxy group, a C1-10 alkylthio group, a carboxyl group, an amine group, an ester group, an amide group, a cyano group, a nitro group and an azido group.
2. The organic compound according to claim 1, characterized in that The organic compound has one or more of the following characteristics: Ar is selected from the following functional groups: wherein R is a hydrogen atom, a halogen atom, a carboxyl group, an amine group, an ester group, an amide group, a C1-C10 alkoxy group, a cyano group, a nitro group or an azido group, X is O, S or Se, and the aromatic ring of the functional group has two connection sites for connecting to other parts of the organic compound; R1 and R2 are each independently selected from C1-C10 alkyl and C1-C10 alkoxy; R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C10 alkoxy group, a C1-C10 alkylthio group, an ester group and a cyano group; R5 and R6 are each independently selected from C1-C20 alkyl groups.
3. The organic compound according to claim 1, characterized in that The organic compound has one or more of the following characteristics: Ar Wherein, * indicates the connection site where Ar is connected to other parts of the organic compound; R1 and R2 are each independently selected from C1-C4 alkyl and C1-C4 alkoxy; R3 and R4 are each independently selected from a hydrogen atom, a halogen atom, a C1-C4 alkoxy group, a C1-C4 alkylthio group, an ester group and a cyano group; R5 and R6 are each independently selected from C1-C10 alkyl groups.
4. The organic compound according to claim 1, characterized in that The organic compound is selected from one or more of compounds 1-9:
5. A light conversion film for sunlight wavelength conversion, characterized in that: The light-converting adhesive film comprises the organic compound described in any one of claims 1-4.
6. The light-converting adhesive film according to claim 5, characterized in that: The mass fraction of the organic compound in the light conversion adhesive film is 0.01% to 5%.
7. The light-converting adhesive film according to claim 5, characterized in that: The mass fraction of the organic compound in the light conversion adhesive film is 0.2% to 0.5%.
8. The light-converting adhesive film according to claim 5, characterized in that: The light-converting adhesive film has one or more of the following characteristics: The absorption range of the organic compound is 280-400nm, and the maximum absorption peak is 320-380nm; The photoluminescence range of the organic compound is 400-600nm, and the maximum emission peak is 450-550nm; The thickness of the light-converting adhesive film is 0.1-1.0 mm.
9. The light-converting adhesive film according to claim 5, characterized in that: The light-converting adhesive film further comprises one or more auxiliary agents selected from the group consisting of a cross-linking agent, an auxiliary cross-linking agent, a silane coupling agent, a plasticizer, an antioxidant and a water absorbent.
10. The light-converting adhesive film according to claim 5, characterized in that: The light-converting adhesive film also includes a matrix.
11. The light-converting adhesive film according to claim 10, characterized in that: The light-converting adhesive film has one or more of the following characteristics: The matrix is one or more selected from polyethylene oxide, ethylene-vinyl acetate copolymer, polyvinyl butyral, ethylene-octene copolymer and silicone resin; The refractive index of the matrix is 1.4 to 1.
7.
12. A method for preparing the light conversion adhesive film according to any one of claims 5 to 11, characterized in that: The method comprises: uniformly mixing the components of the light-converting adhesive film, and then melting and extruding the mixture into a film.
13. A solar cell module, characterized in that: The solar cell assembly comprises a solar cell and a light conversion adhesive film according to any one of claims 5 to 11 arranged on at least one surface of the solar cell.
14. The solar cell assembly according to claim 13, wherein: The solar cell includes one or more of the following cells: a PN cell containing III-V or II-IV group elements, a Cu-In-Ga-Se thin film cell, an organic sensitizer cell, an organic thin film cell, a quantum dot thin film cell, a perovskite cell, a perovskite / crystalline silicon stacked cell, an amorphous silicon solar cell, a microcrystalline silicon solar cell and a crystalline silicon solar cell.
Citation Information
Patent Citations
Thiophene-quinoxaline unit fluorene copolymers, their preparation methods and applications
CN102276802A
Solar cell module with high photoelectric conversion efficiency and manufacturing method thereof
CN106189932A
Quinoxaline-based conjugated polymer, and preparation method and application thereof in polymer solar batteries
CN108948327A
Light conversion adhesive film composition, light conversion adhesive film and photovoltaic module
CN117431022A
Fluorine-containing benzotriazolyl fluorescent compound for light conversion film and synthesis method of fluorine-containing benzotriazolyl fluorescent compound
CN117510421A
Cited By
Tetraphenyl ethylene-benzotriazole derivative compound and application thereof in photovoltaic field
CN121949226A
Light conversion encapsulant film based on quinoxaline-based light conversion material
WO2026144552A1